Prevalencia de parasitismo intestinal en la comunidad Seminke del resguardo indígena Wiwa de la Sierra Nevada de Santa Marta, 2014 (2015)
Introduction: it has been reported, in Latin America, highs parasitism prevalent activities in indigenous communities, considered as a health public problem. In Colombia, studies in these offerings are few, but these studies show similar prevalence. Objective: To determine the general and specific gastrointestinal parasite prevalence, and related factors in the indigenous community of Seminke of Wiwa shelter, in Sierra Nevada de Santa Marta, 2014. Methods: Cross-sectional study in indigenous population, where information collection is enhanced by a social-health survey, and analysis pro triplicate samples of fecal matter subsequence of a Mini Parasep sf. concentration. The description of the population was carried out with summary measures and then the variables were compared through chi-square tests of Pearson and Mann-Whitney, taking into account a significance value of 0.05 in SPSS 21.0. Results: 81 Indigenous were included with a mean age of 19 years (2 months-93 years), finding a parasitism of 96.4%, with 94% of polyparasitism, up to 9 agents per person, versus 97.6% of protozoa to 27.7% of helminths which 67.5% were pathogens. Among the most prevalent species, it was found Blastocystis spp with 94%, Endolimax nana 89.2%, E. coli 84.3%, E. histolytica/E. dispar 55.4% and 44.6% Giardia intestinalis. It was found several statistics according with the gender, not use any treatment for drinking water, the way to eliminate waste, indoor air relationship with animals and the use of shoes. Conclusion: it was found the highest prevalence reported among studies of indigenous communities in Colombia, it was found as risk factors; absence of water treatment; the waste treatment and the intra- or extra-domestic coexistence with animals. © 2015 iMedPub.